Proposal for Reform of the Political Party Regime and the Relationship with National Development - Barrios Espinoza, Jose Luis (2019)
At present, the political parties have grown in number, but not in the quality of their operation, this low performance has a direct impact on the valuation of the population and the development of the country, for which reason, the research aims to: establish the relationship between the proposed reform of the political party regime and national development. The study presents a quantitative approach, correlational-explanatory modality and a non-experimental design of a Transsectional nature. The population was made up of the citizens of Lima, as shown by 68 citizens, located in markets, supermarkets and shopping centers, to which a survey and 5 technical experts in political party systems were applied to which they were interviewed for a total of 73 individuals belonging to the sample. For the analysis of the information the statistical procedure was used by means of the codification and tabulation of the information, this process consisted of the classification and ordering in tables. It´s concluded that the design of a proposal to reform the political party regime is directly and significantly related to national development, as evidenced by the results obtained in the hypothesis test process, where the Correlation with a level of significance of 5% turned out to be significant at the 0.01 level (2 tails) where p <0.05; consequently, the null hypothesis (Ho) was rejected and the alternate hypothesis (Ha) was accepted.